Prosecution of International Crimes - a Historical and Empirical Overview - Rikhof, Joseph (Bergen Journal of Criminal Law & Criminal Justice, 2014)
This article will discuss the manner in which both international institutions as well as domestic courts have dealt with the phenomenon of meeting out justice to persons who have committed the international crimes of genocide, crimes against humanity and war crimes. The paper will begin by painting with a broad brush a canvas of the attempts made at the international level in this area followed by a description of some overarching elements of two types of domestic trials. The first concerns trials conducted in countries relying on territorial jurisdiction, i.e. where the crimes had occurred, while the second is relevant in countries using universal jurisdiction, i.e. where the perpetrator was found after having committed the crimes. The article will then move from the general to one specific aspect of international trials, namely the methodologies used to draw the circle of guilty perpetration of persons involved in international crimes.